Evaluasi Strategi Pengembangan Pemasaran Berkelanjutan berbasis Kearifan Lokal Bagi Industri Rumahan Tempe Bungkus Daun Pisang - Dhiah Wahyu Nur Cahyani; Yenni Kurnia Gusti (LPPM Institut Pendidikan Nusantara Global, 2026)
The banana leaf wrapping tempeh home industry is a form of traditional food business that has economic, social, and cultural value, especially in rural areas. However, in the midst of increasing market competition and changes in people's consumption patterns, the industry faces various challenges, especially in terms of marketing and business sustainability. This research aims to evaluate the conditions of implementing marketing strategies, identify the application of local wisdom values, and formulate sustainable marketing development strategies based on local wisdom in the banana leaf wrapping tempeh home industry in Menadi Village, Pacitan. The results of the study show that the marketing strategy implemented has included elements of the marketing mix (product, price, distribution, and promotion), but it is still traditional and based on social relations. The values of local wisdom such as honesty, precision, mutual cooperation, and the use of banana leaves as natural packaging have been significantly integrated in marketing activities and become the advantages of product differentiation. The recommended sustainable marketing development strategy is an integrative strategy based on the principles of the Triple Bottom Line (profit, people, planet) by emphasizing strengthening local product identity, relational marketing, the use of eco-friendly packaging, and simple promotions based on stories and consumer experience. This strategy is considered to be able to increase business competitiveness without eliminating the traditional character and local cultural values that are the main identity of the tempeh home industry in Menadi Village.